Developing a Sustainable Cardiovascular Disease Research Strategy in Tanzania Through Training: Leveraging From the East African Centre of Excellence in Cardiovascular Sciences Project - Chillo, Pilly; Mashili, Fredirick; Kwesigabo, Gideon; Ruggajo, Paschal; Kamuhabwa, Appolinary (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Cardiovascular disease (CVD) contribute the largest mortality burden globally, with most of the deaths (80% of all deaths) occurring in low and middle-income countries (LMICs), including Tanzania. Despite the increasing burden, to date, CVD research output is still limited in Tanzania, as it is for many sub-Saharan Africa (SSA) countries. This trend hinders the establishment of locally informed CVD management and policy changes. Here, we aim to review the existing gaps while highlighting the available opportunities for a sustainable CVD research strategy in Tanzania. Methods: A rapid review of available literature on CVD research in SSA was conducted, with emphasis on the contribution of Tanzania in the world literature of CVD. Through available literature, we identify strategic CVD research priorities in Tanzania and highlight challenges and opportunities for sustainable CVD research output. Findings: Shortage of skilled researchers, inadequate research infrastructure, limited funding and lack of organized research strategies at different levels (regional, country and institutional) are among the existing key bottlenecks contributing to the low output of CVD research in Tanzania. There is generally strong global, regional and local political will to address the CVD epidemic. The establishment of the East African Centre of Excellence in Cardiovascular Sciences (EACoECVS) offers a unique opportunity for setting strategies and coordinating CVD research and training for Tanzania and the East African region. Conclusion: There is a light of hope for long-term sustainable CVD research output from Tanzania, taking advantage of the ongoing activities and plans for the evolving EACoECVS. The Tanzanian experience can be taken as a lesson for other SSA countries.